2022
DOI: 10.1088/1674-1056/ac754f
|View full text |Cite
|
Sign up to set email alerts
|

Progress and challenges in magnetic skyrmionics

Abstract: Magnetic skyrmions are two-dimensional localized topological spin-structures characterized by the skyrmion number that measures the number of times of spins wrapping the Bloch sphere. Skyrmions behave like particles under an external stimulus and are promising information carriers. Skyrmions can exist as an isolated object as well as skyrmion condensates in crystal structures, helical/conical states, mazes or irregular stripy states with emergent electromagnetic fields. Thus, skyrmions provide a nice platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 167 publications
0
7
0
Order By: Relevance
“…The efficient controlling topological charge is one of the most important fundamental problems in realizing skyrmion spin devices. 6,9 It is found that Q > 0 for B ≤ 0, whereas Q < 0 for B > 0 in Janus magnets in the right panel of Fig. 3, Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The efficient controlling topological charge is one of the most important fundamental problems in realizing skyrmion spin devices. 6,9 It is found that Q > 0 for B ≤ 0, whereas Q < 0 for B > 0 in Janus magnets in the right panel of Fig. 3, Fig.…”
Section: Resultsmentioning
confidence: 85%
“…[3][4][5] Furthermore, adjustments in the size and the topological charge are critical for constructing skyrmion-based spintronic devices. 6 Technically, adjustable skyrmions with a diameter of sub-10 nm are one of the requirements for ultradense and high speed skyrmionic nano-devices. However, the sizes of skyrmions in most magnetic materials are much larger than 10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic skyrmions, as topologically protected spin structures characterized by topological charges, have been widely studied in recent years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Skyrmions have the characteristics of small size, topological protection, and low drive current density, which are conducive to the technical applications in high-density data storage equipment and low-energyconsumption spintronic devices. [18][19][20][21][22] In particular, the theoretical application of skyrmions has been extended to antiferromagnetic skyrmions, including racetrack memories, logic devices, spin nano-oscillators, and other promising spintronic devices derived from no spin Hall effect, zero stray field, and ultra-fast magnetization dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic skyrmions are localized topological spin swirls that are potentially applicable in developing spintronic devices, due to their intriguing electromagnetic properties. To achieve high-density skyrmion-based spintronic devices, it is necessary to investigate the geometrical confinement effect of nanostructures related to these devices. ,,, Previous studies have demonstrated the stabilization of skyrmions in nanodisks, , nanostripes, triangles, and tetrahedrons . Skyrmions exhibit remarkable stability and emergent topological magnetism in confined low-dimensional geometries. …”
mentioning
confidence: 99%
“…1−12 To achieve high-density skyrmion-based spintronic devices, it is necessary to investigate the geometrical confinement effect of nanostructures related to these devices. 3,6,12,13 Previous studies have demonstrated the stabilization of skyrmions in nanodisks, 14,15 nanostripes, 16 triangles, 17 and tetrahedrons. 18 Skyrmions exhibit remarkable stability and emergent topological magnetism in confined low-dimensional geometries.…”
mentioning
confidence: 99%